ANALISIS USAHATANI AREN (Arenga pinnata Merr) DI KOTA TOMOHON, SULAWESI UTARA - Manambangtua, Alfred P; Hutapea, Ronald T.P.; Wungkana, Jerry (Jurnal Sosial Ekonomi Pertanian, 2018)
Abstract Aren (Arenga pinnata Merr) is a type of palm that has a fairly high economic value, is spreading widely in Indonesia. All parts of the sugar plant ranging from leaves to roots can be utilized. The main result is the sap of the sugar plant, sugar palm juice contains between 10-15%. Because the sugar content of the sugar palm can be processed into alcohol, palm sugar, palm syrup, palm vinegar and ethanol. Based on the analysis results obtained, sugar palm farmers monthly fee of Rp. 2,196,815, - and Rp 26 361 780, - per year. Average monthly revenues of Rp 4.1236 million, - and Rp 49.483.200, - per year. Palm farmers' income of Rp 1,926,785, - and Rp 23.121.420, - per year. Analysis of R / C Ratio > 1 is 1.88, which means businesses aren farmer in Tomohon is getting Keywords : revenue; income; cost; aren farmers